A step change in the transfer of interspecific variation into wheat from Amblyopyrum muticum - King, Julie; Grewal, Surbhi; Yang, Cai-yun; Hubbart, Stella; Scholefield, Duncan; Ashling, Stephen; Edwards, Keith J.; Allen, Alexandra M.; Burridge, Amanda; Bloor, Claire; Davassi, Alessandro; da Silva, Glacy J.; et al. (Wiley Open Access, 2016)
Despite some notable successes, only a fraction of the genetic variation available in wild relatives has been utilized to produce superior wheat varieties. This is as a direct result of the lack of availability of suitable high-throughput technologies to detect wheat/wild relative introgressions when they occur. Here, we report on the use of a new SNP array to detect wheat/wild relative introgressions in backcross progenies derived from interspecific hexaploid wheat/Ambylopyrum muticum F₁ hybrids. The array enabled the detection and characterization of 218 genomewide wheat/Am. muticum introgressions, that is a significant step change in the generation and detection of introgressions compared to previous work in the field. Furthermore, the frequency of introgressions detected was sufficiently high to enable the construction of seven linkage groups of the Am. muticum genome, thus enabling the syntenic relationship between the wild relative and hexaploid wheat to be determined. The importance of the genetic variation from Am. muticum introduced into wheat for the development of superior varieties is discussed.